PENDAYAGUNAAN ILMU TEKNOLOGI KOMPUTER DITINJAU DARI SUDUT IMAN KRISTEN - Benget Rumahorbo (Universitas Methodist Indonesia, 2015)
The advancement of of computer science has changed the world from wide to tight;long to short;uneasy to easy. Computer technology has made the world unlimited. By finding the formulations of computer new capacity like it has been able to replace the position of human's brain in any knowledge and activities. In other words, the progress of computer science which has been reached till now has been truely avowed by world. Computer gives facilities and pleasure in life. In the reality computer has given the contribution to human's culture and prosperity. However human can't resist the reality that computer science has also given damage and misery to people. The reality from the life now is computer technology is able to reveal the secret of nature and life, but it is not the same as the truth. In other words computer is just able to give the reality. Meanwhile the truth is not humane. The humane truth is not only that but it must be objective which cover the justice. Computer technology doesn't know the solution of human's moral, so human mostly use the computer technology for amoral things and influences human's attitude in the real life. Based on the reality, recently computer has been used for criminal behavior, so it must be behaved from the truth of Allah saying. So people do not abuse computer to negative things but for the positive things.